Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2019
DOI: 10.1111/cas.14209
|View full text |Cite
|
Sign up to set email alerts
|

Activity of TAS4464, a novel NEDD8 activating enzyme E1 inhibitor, against multiple myeloma via inactivation of nuclear factor κB pathways

Abstract: The ubiquitin proteasome pathway is essential for the proliferation and survival of multiple myeloma (MM) cells. TAS4464, a novel highly potent inhibitor of NEDD8 activating enzyme, selectively inactivates cullin-RING ubiquitin E3 ligases, resulting in accumulation of their substrates. Here, we examined 14 MM cell lines treated with TAS4464. TAS4464 induced growth arrest and cell death in the MM cell lines even in the presence of bone marrow stromal cells. It also induced the accumulation of phospho-inhibitor … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 41 publications
1
12
0
Order By: Relevance
“…We previously reported the inhibitory effect of TAS4464 on the neddylation pathway in several hematopoietic cancers [ 27 , 31 ], and in this study, a similar drug functionality of TAS4464 was shown in AML cell lines by confirming the decrease in NEDD8 conjugation by Ubc12 or cullin1 (Fig. 3A ).…”
Section: Resultssupporting
confidence: 86%
“…We previously reported the inhibitory effect of TAS4464 on the neddylation pathway in several hematopoietic cancers [ 27 , 31 ], and in this study, a similar drug functionality of TAS4464 was shown in AML cell lines by confirming the decrease in NEDD8 conjugation by Ubc12 or cullin1 (Fig. 3A ).…”
Section: Resultssupporting
confidence: 86%
“…In preclinical analyses, the antiproliferative effects of TAS4464 increased in a dose- and time-dependent manner, plateauing after 24 h. Additionally, TAS4464 demonstrated promising antitumor effects in several hematologic and solid tumor xenograft models without notable weight loss [ 13 ]. Further, in vitro and in vivo investigations of TAS4464 in multiple myeloma models found that the antitumor activity of TAS4464 occurs through inhibition of nuclear factor κB (NFκB) activation, thereby affecting the canonical and noncanonical NFκB pathways [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…TAS yielded significantly reduced tumor burden in the THP-1 xenograft model of AML as well as a patient derived xenograft (PDX) model of small cell lung cancer [64,65]. TAS has also been reported to display significant antitumor activity in a xenograft model of multiple myeloma (MM) when combined with various standard of care agents [66]. Together, these results demonstrate the potential of TAS for therapeutic use in a wide variety of cancer types.…”
Section: Tas4464mentioning
confidence: 81%